Application of Proline-Derived (Thio)squaramide Organocatalysts in Asymmetric Diels–Alder and Conjugate Addition Reactions - Dargó, Gyula; Nagy, Sándor; Kis, Dávid; Bagi, Péter; Mátravölgyi, Béla; Tóth, Blanka; Huszthy, Péter; Drahos, László; Kupai, József (Synthesis, 2022)
The synthesis of chiral proline-derived squaramide and thiosquaramide organocatalysts, which are capable of the dual activation in asymmetric reactions is reported. The (thio)squaramide moiety can form hydrogen bonds to activate the substrates and to stereocontrol the reaction, while the pyrrolidine unit can form enamines to activate carbonyl compounds via aminocatalysis. Comparing the performance of thiosquaramide to squaramide, the Diels–Alder reaction of (anthracen-9-yl)acetaldehyde and trans-β-nitrostyrene was examined, which has been investigated in the literature using quantum chemical calculations. Both squaramide and thiosquaramide gave excellent yields (up to 99%) and enantiomeric excess values (up to 98%). Moreover, their catalytic performance was compared in conjugate addition of lawsone to β,γ-unsaturated α-keto ester.
Keywords: asymmetric organocatalysis; aminocatalysis; proline; thiosquaramide; Diels–Alder reaction; conjugate addition